Downregulation of clusterin mediates sensitivity to protein kinase inhibitors in breast cancer cells. Issue 1 (January 2015) - Redondo, Maximino; García-Aranda, Marilina; Roldan, Maria J.; Callejón, Gonzalo; Serrano, Alfonso; Jiménez, Eugenio; Téllez, Teresa
Abstract : The efficacy of protein kinase inhibitors (PKIs) has been shown in clinical assays for cancer, but as isolated agents, they only have a modest effect. One of the most important characteristics of mitogen-activated PKIs is their ability to decrease the apoptotic threshold of cancer cells, sensitizing them to the action of other antiapoptotic agents. The secretory clusterin protein is an inhibitor of apoptosis with a cytoprotective function. We describe the use of clusterin-specific antisense oligonucleotides and siRNA to sensitize breast carcinoma cells to several PKIs. MCF-7 and MDA-MB-231 cells were treated with antisense oligonucleotide or siRNA to clusterin and the following PKIs: H-89, chelerythrine and genistein. The three inhibitors used in this study upregulated clusterin expression and treatments that included antisense oligonucleotide or siRNA to clusterin reduced the number of viable cells more effectively than did treatment with the drugs alone. Therefore, treatment with such combinations may benefit patients with breast cancer.